THE NUTRITIONAL STATUS OF TODDLERS IS A RISK FACTOR FOR MALARIA INCIDENCE AT KIMI HEALTH CENTER - Popang, Christina Tien; Isnaini, Yuni Subhi; Mulyanti; Ester (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Malaria remains a global health issue, particularly in tropical and subtropical regions. In Indonesia, Papua Province specifically Nabire Regency reports a high incidence of malaria, although a decline has been observed since 2010. Infants and pregnant women are the most vulnerable groups. Nutritional status, influenced by dietary patterns, environment, and access to healthcare, plays a crucial role in susceptibility to malaria. Malnourished children are more prone to severe malaria infections due to their underdeveloped immune systems. This research focuses on Kimi Health Center in Nabire Regency and aims to explore the relationship between the nutritional status of children under five and malaria incidence in 2024. The goal of this study is to determine the relationship between the nutritional status of children under five and malaria incidence at Kimi Health Center, Teluk Umar District, Nabire Regency, in 2024. The research design employs an analytical descriptive approach with a cross-sectional method to analyze the relationship between nutritional status and malaria incidence. Data was collected at one point in time and analyzed using univariate and bivariate analysis with the Kendall tau-b test through SPSS software. The results show that nutritional status significantly influences susceptibility to malaria. Children with poor nutrition are at a higher risk of experiencing severe malaria due to immune system dysfunction. Malnutrition, such as Protein-Energy Malnutrition (PEM), worsens parasitemia and anemia. Nutrient deficiencies, including iron, vitamin A, and zinc, also weaken the immune system. Therefore, improving nutritional status is a crucial effort in malaria control within endemic areas.